Leaching patterns from wood of different tree species and environmental implications related to wood storage areas. (21st February 2013) - Svensson, Henric; Marques, Marcia; Kaczala, Fabio; Hogland, William
Abstract Batch tests were carried out with sawdust obtained from oak (Quercus robur), maple (Acer platanoides), pine (Pinus sylvestris), beech (Fagus sylvatica) and wood chips from oak and pine. Leaching of organic compounds expressed as dissolved organic carbon (DOC) in mg/kg of dry mass took place during the first 24 h. The following additional variables were analysed: pH, conductivity, colour, phenols, tannins and lignin, and biochemical oxygen demand (BOD7). When leachates obtained with oak wood chips and pine wood chips were compared, no significant difference was observed. However, in batch tests with sawdust, DOC released by oak (90 000 mg/kg) was significantly higher (P = 0.0001) than DOC released by pine (30 000 mg/kg). The results suggest that particle size is not the only variable affecting the leaching of organic compounds from wood. Regarding BOD, colour [platinum‐cobalt (Pt‐Co)], phenols, tannins and lignin, the leaching patterns differed among species, and oak was the species with the highest released values.